Dual enzyme-mimic nanozyme based on single-atom construction strategy for photothermal-augmented nanocatalytic therapy in the second near-infrared biowindow. (February 2022) - Su, Yutian; Wu, Fan; Song, Qiuxian; Wu, Mengjie; Mohammadniaei, Mohsen; Zhang, Taiwei; Liu, Baolei; Wu, Shishan; Zhang, Ming; Li, Ao; Shen, Jian
Abstract: Nanozyme-based catalytic therapy, an emerging therapeutic pattern, has significantly incorporated in the advancement of tumor therapy by generating lethal reactive oxygen species. Nevertheless, most of the nanozymes have mono catalytic performances with H2 O2 in the tumor microenvironment (TME), which lowers their therapeutic efficiency. Herein, we design a newly-developed single-atom Fe dispersed N -doped mesoporous carbon nanospheres (SAFe-NMCNs) nanozyme with high H2 O2 affinity for photothermal-augmented nanocatalytic therapy. The SAFe-NMCNs nanozyme possesses dual enzyme-mimic catalytic activity which not only acts as a catalase-mimic role to achieve ultrasonic imaging in tumor site by O2 generation, but also exhibits the superior peroxidase-mimic catalytic performance to generate OH for nanocatalytic therapy. Besides, the SAFe-NMCNs nanozyme with strong optical absorption in the second near-infrared (NIR-II) region shows excellent photothermal conversion performance. The peroxidase-mimic catalytic process of SAFe-NMCNs nanozyme is realized using density functional theory (DFT). Both in vitro and in vivo results indicate that the SAFe-NMCNs nanozyme can efficiently suppress tumor cells growth by a synergistic therapy effect with photothermal-augmented nanocatalytic therapy. The work developed a single-atom-coordinated nanozyme with dual-enzyme catalytic performance and achieve hyperthermia-augmented nanocatalytic therapy effect, can open a window for potential biological applications.